Transcriptomic Analysis, Motility and Biofilm Formation Characteristics of Salmonella typhimurium Exposed to Benzyl Isothiocyanate Treatment - Niu, Tong-Xin; Wang, Xiao-Ning; Wu, Hong-Yan; Bi, Jing-Ran; Hao, Hong-Shun; Hou, Hong-Man; Zhang, Gong-Liang (International Journal of Molecular Sciences, 2020)
Salmonella typhimurium (S. typhimurium) is a common foodborne pathogen that not only causes diseases and contaminates food, but also causes considerable economic losses. Therefore, it is necessary to find effective and feasible methods to control S. typhimurium. In this study, changes in S. typhimurium after treatment with benzyl isothiocyanate (BITC) were detected by transcriptomics to explore the antibacterial effect of BITC at subinhibitory concentration. The results showed that, in contrast to the control group (SC), the BITC-treated group (SQ_BITC) had 197 differentially expressed genes (DEGs), of which 115 were downregulated and 82 were upregulated. We screened out eight significantly downregulated virulence-related genes and verified gene expression by quantitative Real-time Polymerase Chain Reaction (qRT-PCR). We also selected motility and biofilm formation to observe the effects of BITC on the other virulence related factors of S. typhimurium. The results showed that both swimming and swarming were significantly inhibited. BITC also had a significant inhibitory effect on biofilm formation, and showed an effect on bacterial morphology. These results will be helpful for understanding the mechanism of the antibacterial action of BITC against S. typhimurium and other foodborne pathogens.